2023
DOI: 10.3390/jcm12196397
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Survival Impact of Delayed Graft Function Depends on Kidney Donor Risk Index: A Single-Center Cohort Study

Joseba Salguero,
Laura Chamorro,
Enrique Gómez-Gómez
et al.

Abstract: Background: Delayed graft function (DGF) is a significant challenge in renal transplantation, particularly with deceased donors, necessitating early postoperative dialysis. The prolonged effects of medium- and long-term DGF remain uncertain, marked by contradictory graft survival outcomes. This incongruity might arise from the inherent graft resilience and regenerative capacity during transplantation. This study investigates DGF’s impact on graft survival, focusing on grafts displaying favorable (KDRI < 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Higher KDPI values have been associated with increased risk for DGF [3,[10][11][12]. The effects of KDPI on graft survival have been studied using mixed cohorts of both EF and DGF kidneys, and a few studies could be found where the impact of KDPI had been studied on a DGF population [7,26]. One of these studies showed that KDPI >85% was associated with worse outcomes in both EF and DGF kidneys which was confirmed in our study of a larger cohort [7].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Higher KDPI values have been associated with increased risk for DGF [3,[10][11][12]. The effects of KDPI on graft survival have been studied using mixed cohorts of both EF and DGF kidneys, and a few studies could be found where the impact of KDPI had been studied on a DGF population [7,26]. One of these studies showed that KDPI >85% was associated with worse outcomes in both EF and DGF kidneys which was confirmed in our study of a larger cohort [7].…”
Section: Discussionsupporting
confidence: 82%
“…As donors with KDPI >85% have been compared to the earlier used designation extended criteria donors [12], a worse graft survival estimate of these kidneys is in line with earlier research. Another study showed increased risk of graft loss in DGF kidneys with kidney donor risk index >1 [26]. One study examined the risk of DGF and graft loss in standard vs. extended criteria donors from both braindead donors and DCD donors.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of immediate function, known as delayed graft function (DGF), commonly defined as the need for dialysis during the first week after transplantation, is a well-known risk factor for worse graft function in kidney transplantation [7][8][9][10][11], even in the absence of acute rejection [8,11,12]. DGF has an incidence ranging between 10% and 50% of deceased-donor kidney transplantations [7,8,[10][11][12][13][14][15][16][17], but its incidence may raise to 63% in kidney transplants from marginal donors [18]. The most important risk factors for DGF are older donor age, donor acute kidney injury, older recipient age and prolonged cold ischemia time [7,8,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…DGF has an incidence ranging between 10% and 50% of deceased-donor kidney transplantations [7,8,[10][11][12][13][14][15][16][17], but its incidence may raise to 63% in kidney transplants from marginal donors [18]. The most important risk factors for DGF are older donor age, donor acute kidney injury, older recipient age and prolonged cold ischemia time [7,8,[10][11][12][13][14][15][16][17]. The donor's age has a clear impact on the incidence of DGF and, therefore, to reduce the incidence of DGF in kidney transplantation from marginal donors, many centers have adopted a policy of local allocation of kidneys to pre-consented candidates, in most cases obviating biopsy, and by reducing the cold ischemia time, they lowered the incidence of DGF [19,20].…”
Section: Introductionmentioning
confidence: 99%